Temperature‐dependent Li isotope ratios in Appalachian Plateau and Gulf Coast Sedimentary Basin saline water. Issue 4 (29th July 2014) - Macpherson, G. L.; Capo, R. C.; Stewart, B. W.; Phan, T. T.; Schroeder, K.; Hammack, R. W.
Abstract: Lithium (Li) concentrations of produced water from unconventional (horizontally drilled and hydraulically fractured shale) and conventional gas wells in Devonian reservoirs in the Appalachian Plateau region of western Pennsylvania range from 0.6 to 17 mmol kg −1, and Li isotope ratios, expressed as in δ 7 Li, range from +8.2 to +15‰. Li concentrations are as high as 40 mmol kg −1 in produced waters from Plio‐Pleistocene through Jurassic‐aged reservoirs in the Gulf Coast Sedimentary Basin analyzed for this study, and δ 7 Li values range from about +4.2 to +16.6‰. Because of charge‐balance constraints and rock buffering, Li concentrations in saline waters from sedimentary basins throughout the world (including this study) are generally positively correlated with chloride (Cl), the dominant anion in these fluids. Li concentrations also vary with depth, although the extent of depth dependence differs among sedimentary basins. In general, Li concentrations are higher than expected from seawater or evaporation of seawater and therefore require water–mineral reactions that remove lithium from the minerals. Li isotope ratios in these produced waters vary inversely with temperature. However, calculations of temperature‐dependent fractionation of δ 7 Li between average shale δ 7 Li (−0.7‰) and water result in δ 7 Liwater that is more positive than that of most produced waters. This suggests that aqueous δ 7 Li may reflect transport of water from depth and/or reaction with rocks having δ 7 Li lighter than average shale. Abstract : Lithium, compiled from oil and gas field fluids around the world, correlates generally with depth and with Cl, confirming water–rock interactions are its primary source. δ 7 Li of Appalachian Plateau and Gulf Basin (USA) water ranges from +4.4‰ to +16.6‰ and follows a coherent temperature trend, despite differences in tectonic histories of the two basins. Equilibrium isotope fractionation predicts a Li source material that is approximately 4‰ lighter than average shale δ 7 Li.